Experiences and self-care of pregnant nurses with gestational diabetes mellitus: a qualitative study - Jing He; Hui Wang; Xiaoli Chen (BMC, 2024)
Abstract Background Pregnant nurses are at high risk of developing gestational diabetes mellitus (GDM), and nurses diagnosed with GDM face challenges in balancing disease management and work, which affects maternal and child health and the quality of care. GDM requires significant changes to lifestyle and physical activity to control blood glucose levels, which is key to reducing adverse pregnancy outcomes. However, few studies have focused on the experiences of pregnant nurses with GDM. This study aimed to gain insight into the experiences of pregnant nurses with GDM in China in terms of their illness, work burdens, and self-care. Methods This qualitative study used an interpretative phenomenological analysis. Face-to-face semi-structured in-depth interviews were conducted with pregnant nurses with GDM to investigate their experiences and self-care. The study was performed at Chongqing's maternal and child health hospital in China. A purposive sampling was used. Nine pregnant nurses diagnosed with GDM were recruited and interviewed. Results The interview data generated four themes and 11 sub-themes. The four themes were 'the perceptions and feelings of GDM', 'experiences of lifestyle changes', 'social support needs', and 'health expectations and risk perception.' Conclusion Many factors such as the unique occupational environment, overwork, occupational pressure, shift work, family status, and education level may lead to difficulties in managing blood glucose in nurses with GDM. These findings suggest that managers should pay more attention to nurses with GDM and develop personalized medical care and work arrangements. These measures can improve the self-care and well-being of nurses with GDM and promote the health of nurses and their offspring.